Resinas compostas bulk-fill : avaliação da deflexão de cúspides, da adaptação e do selamento marginal - Duarte, Renata Webster (2019)
The aim of the study was to evaluate, ex vivo, the cusp deflection, adaptation and marginal sealing of class II cavities restored with bulk-fill composite resins. Class II preparations were performed in 44 human premolars (mesial box 1 mm below the CEJ, distal box 1 mm above CEJ) and were randomly divided into 4 groups (n=11): G1 (control): Filtek Z250 XT; G2: Filtek Bulk-Fill; G3: Tetric NCeram Bulk-Fill; G4: Aura Bulk-Fill. After cavitiy preparation, cuspal deflection measurements were obtained with the aid of a digital micrometer. The Single Bond Universal adhesive system was applied, the cavities were restored, and new cuspal deflection measurements were obtained. Impressions were made using polyvinyl siloxane and epoxy resin replicas were obtained, before and after thermocycling. The cervical margins were analyzed with SEM at 200x magnification. The marginal adaptation was expressed as percentages of continuous margins. After thermocycling, the specimens were immersed in silver nitrate 50%, and analyzed the extention of dye penetration in the cervicalmesial and cervical-distal margins. According to ANOVA test, there was no significant difference in the cusp deflection means between the groups (p= 0.127). Kruskal-Wallis and Mann-Whitney tests showed no significant difference in the percentage of continuous margins between the groups, as well as before and after thermocycling (p>0.05). According to Kruskal-Wallis test, there was no significant difference in the microleakage scores between the enamel margin groups (p = 0.249). Nemenyi test showed significant difference between group 1 and group 3 (p=0.010) at the dentin margin. According to Wilcoxon test, dentin microleakage scores were significantly higher than the enamel scores for group 3 (p=0.0025) and group 4 (p=0.0004). It was concluded that bulk-fill composite resins presented similar behavior to conventional composite resin in relation to cusp deflection, adaptation and marginal sealing.